Effects of pregnancy on skin properties: A biomechanical approach. Issue 4 (26th February 2018) - Boyer, G.; Lachmann, N.; Bellemère, G.; De Belilovsky, C.; Baudouin, C.
Abstract: Background: A woman's skin is dramatically affected by pregnancy. Its biomechanical properties are critical for resisting highly stressed areas. The aim of this work was to evaluate the impact of pregnancy on the mechanical properties of skin, as well as to evaluate the imprint that pregnancy leaves on the skin after delivery. Materials and Methods: Suction tests using a cutometer were performed on 15 non‐pregnant women and 26 pregnant women at 8 months of pregnancy and 4 months after delivery. Areas of abdomen and thighs were studied. Results: Significant differences between the non‐pregnant and 8‐month pregnant groups were observed. Our data demonstrate that skin becomes less elastic and less deformable on the abdomen during pregnancy. On the thighs, a loss of elasticity and firmness was also observed. At 4 months after delivery, the skin did not return to its initial state. Conclusion: This study showed that the mechanical properties of skin changed drastically during pregnancy compared to the non‐pregnant condition and that these properties remain altered 4 months after delivery. In addition to alterations in abdominal skin during pregnancy, we also observed mechanical changes on the thighs, which are less subject to stretching.